EFFECTIVENESS OF NETWORKED LEARNING IN SCHOOLS (REDIRECTED FROM KUTTAB AL FATIH BEJI DEPOK) - Deni Nugraha, Asep; Rafid, Rahmad (Four Son Scholarship, 2023)
In general, this study aims to determine the effectiveness of online learning at the Kuttab Al Fatih Beji School, Depok. This research uses case study qualitative research methods and data collection tools using interviews, observations and document studies. Data analysis uses reduction, data presentation and verification. Informants in this study were teachers as main informants as many as 5 people and students as supporting informants as many as 10 people at Kuttab Al Fatih Beji School, Depok. The results of this study indicate the effectiveness of learning in the network, namely learning can be done anywhere and anytime without being limited by time. The effectiveness of Kuttab education includes Kuttab in accordance with the concept of education built by the Prophet, more freedom in making curriculum according to the vision and mission; recognized syar'i against secularism, restore the role of parents as primary educators; in line with the goals of National education, to be a solution to existing educational problems, namely adab or character; more effective, namely diniyah education is more dominant, while general knowledge is only taken that is useful (ulumun nafi'ah), more flexible in managing school management, coordination and evaluation is easier because of the similarity of vision and mindset of the educators; not busy with a lot of administration. Obstacles in implementing education during the Covid-19 pandemic are the reduction in time during the pandemic causing curriculum achievements to be adjusted to conditions; there is value lost when learning is done online; students' different understandings; signal and device constraints in the network; cannot directly control the implementation of children's faith and etiquette; The solution to these obstacles is the selection of the material to be delivered according to the conditions; learning activities through zoom meetings so that they can meet face to face; create study groups or home visits; strive for face-to-face learning; charity control in collaboration with parents with a check list with google form. The application of online or online learning at Kuttab Al-Fatih Beji includes: making videos and audio of KBM faith classes, videos of Al-Qur'an material, adab, and motivation for learning Al-Qur'an classes, videos of sports materials, videos of pledge materials , video material for stories and tasmi'as well as online learning directly through zoom meetings. Offline or face-to-face learning is also carried out, but only once a week for the Early Kuttab class and once every two weeks for the Qonuni class